1997
DOI: 10.1159/000121234
|View full text |Cite
|
Sign up to set email alerts
|

Choroid Plexus Papilloma and Cysts in the Aicardi Syndrome: Case Reports

Abstract: Two female infants with callosal agenesis, infantile spasms, chorioretinal lacunae, optic disc colobomas and cortical heterotopias were diagnosed with Aicardi syndrome. A choroid plexus papilloma was found in one patient, and choroid plexus cysts were found in the other. Choroid plexus lesions are common findings in the Aicardi syndrome and are discussed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…The diagnosis of the tumors was made only after MRI. In the majority of cases reporting association of Aicardi disease and choroid plexus papilloma, the tumor was located in only one ventricle 2,4,6,7 . Tackibana et al 3 described a case in which the tumors occupied the right lateral and the third ventricles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The diagnosis of the tumors was made only after MRI. In the majority of cases reporting association of Aicardi disease and choroid plexus papilloma, the tumor was located in only one ventricle 2,4,6,7 . Tackibana et al 3 described a case in which the tumors occupied the right lateral and the third ventricles.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical/radiological manifestations of the Aicardi syndrome 1 , initially described as a triad of infantile spasms, total or partial agenesis of the corpus callosum and retinal changes, now include periventricular and subcortical heterotopias, choroid plexus cysts and tumors, colobomas, skeletal changes of vertebrae and ribs, microphthalmia, cerebral hemispheres asymmetry, cortical gyrus changes, tumors outside of CNS and cranialfacial alteration. A review of the literature [2][3][4][5][6][7] revealed ten cases in which the disease manifested in association with choroid plexus papilloma. These numbers should increase when children with Aicardi syndrome are routinely submitted to TC and/ or MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported choroid plexus papillomas in girls with Aicardi syndrome. 1,22,24,25 Hypomelanosis of Ito is a descriptive condition caused by a variety of chromosomal abnormalities and is often associated with other neurological and skeletal abnormalities. In the setting of an X;17(q12;p13) translocation, hypome- lanosis of Ito has been associated with the development of choroid plexus papillomas.…”
Section: Other Syndromesmentioning
confidence: 99%
“…Several case reports of patients with this syndrome document histologically confirmed choroid plexus papillomas [6, 8, 9, 10, 11, 12]. Others report on associated choroid plexus papillomas as diagnosed by CT or MRI [13, 14].…”
Section: Introductionmentioning
confidence: 99%